Prevalence of bovine fascioliasis and economic losses in an abattoir located in the state of Espírito Santo, Brazil - Teixeira, Jessica Nogueira [UNESP]; Barcellos, Rodrigo Rhoden; Link, Daniella Tosta; Mathias, Luis Antonio [UNESP]; Tobias, Fernando Luiz; Braga, Fabio Ribeiro; Rossi, Gabriel Augusto Marques (Universidade Federal de Santa Maria, 2022)
Bovine fasciolosis is a neglected parasitic zoonosis that causes economic losses to beef production chains due to liver condemnation at abattoirs. Despite the characterization of Bovine fasciolosis in several areas of Brazil, an update on its prevalence in the states of Rio de Janeiro and Espirito Santo is lacking. Thus, fasciolosis prevalence from 2018 to 2021 is presented here according to cattle origin (municipalities of both states). In addition, the associated economic impact on an abbatoir was analyzed through liver condemnation of bovines from both states. The prevalence of fasciolosis in the state of Espírito Santo (10.4%) was significantly higher than Rio de Janeiro (3.6%) (P < 0.01), and resulted in an economic loss of US$12,678.60 for the abattoir. The following municipalities located in the state of Espírito Santo presented prevalences above the mean (10.3%) established in the study: Vargem Alta, Anchieta, Cachoeiro do Itapemirim, Castelo, Atilio Vivacqua, Apiacá and Ibitirama. Thus, majority of these municipalities are considered high-risk areas. Although, there is an aparrent reduction of fasciolosis prevalence, it continues to be a cause of economic losses in abattoirs especially in the state of Espírito Santo. Accordingly, prophylactic measures must still be adopted in cattle farms.

A fasciolose bovina é uma zoonose parasitária negligenciada que resulta em perdas econômicas para a cadeia produtiva da carne devido à condenação de fígado em abatedouros-frigoríficos. Essa doença é descrita em diversas áreas do Brasil, mas existe uma deficiência de informações atuais sobre a prevalência nos estados do Rio de Janeiro e Espírito Santo. Essa nota descreve a prevalência de fasciolose de 2018 a 2021 de acordo com o município de origem e o impacto econômico devido à condenação de fígados em um abatedouro que recebe animais de ambos os estados. A prevalência no Estado do Espírito Santo (10,4%) foi significativamente maior do que no Rio de Janeiro (3,6%) (P < 0,01) e resultou em uma perda econômica de R$ 64.636,00. Os municípios de Vargem Alta, Anchieta, Cachoeiro do Itapemirim, Castelo, Atilio Vivacqua, Apiacá e Ibitirama apresentaram prevalência superior à prevalência desse estudo (10,3%), sendo que esses municípios vem sendo reconhecidos como áreas de alto risco. Apesar de uma aparente redução na prevalência da enfermidade, a fasciolose persiste como uma causa de perdas econômicas aos abatedouros, especialmente no Estado do Espírito Santo, e medidas profiláticas ainda precisam ser adotadas nas fazendas.
Prevalência de fasciolose bovina e perdas econômicas em um abatedouro frigorífico localizado no estado do Espírito Santo, Brasil
Keywords: Fasciola hepatica; liver; meat inspection; parasitology; Fasciola hepatica; fígado; inspeção de carnes; parasitologia